ANALYSIS OF PSYCHOLOGICAL NEEDS OF FLASH FLOOD DISASTER VICTIMS IN TANAH DATAR - khairiyah, ratu; fitriani, wahida; yeni, putri (AGENDA: Jurnal Analisis Gender dan Agama, 2024)
The research results show that victims of the flash flood disaster in tanah datar experienced significant psychological impacts, including trauma, anxiety and sadness. The main psychological needs of victims include emotional support, trauma recovery, mental strengthening, social support, and rehabilitation and recovery. By paying attention to the psychological needs of victims of flash flood disasters, collaborative efforts between emergency relief teams, psychologists, social workers and mental health volunteers can provide holistic and sustainable support for victims. This can provide an in-depth understanding of the psychological needs of victims of the flash flood disaster in Tanah Datar and provide a basis for developing appropriate and effective programs to support the overall recovery of victims.